(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Problematic issues of construction and operation of oil storage vertical steel tanks in complex geotechnical conditions, including the seismically unstable territories are systematized. The technique of seismic danger decreasing (increasing the seismic stability of the ground) for ensuring the accident-free operation of tanks during earthquakes of various intensities is proved. The practical experience of design solutions of the highly effective systems «man-made grounds – foundation – tank» in complex geotechnical conditions for static and dynamic effects (earthquakes, emergency technogenic loadings, etc.) is given.